The Role of Quality Standards (ISO) and International Auditing Standards in the Control and Auditing of the Quality of the Gas Industry - Khawla Hussein Hamdan; Haidar Adel Abbas (Journal of Madenat Alelem University College, 2019)
In light of the increasing needs of the East Asian region to alternative sources of energy for oil from low-cost, low-emission fuels that pollute the environment and natural gas, the researcher sought to shed light on the issues that must be addressed to the specialized companies to extract and produce gas benefit Of the opportunities in the markets to invest natural gas, through the adoption of these companies on the quality standards for the extraction and gas industry to enable these companies to measure variables in light of the needs of the market and consumer, and highlight the most important international auditing standards Including quality management and auditing, based on international sources and standards, laws and regulations in force in Iraq, indicators issued by quality institutions, as well as international agreements related to the gas industry. The most important conclusions reached by the researcher are that quality standards must be used in industry Gas, and the researcher recommended the need to oblige companies producing gas standards.